Food recommender for anemia patient by using rule based / Siti Nurfarizza Abdul Wahab - Abdul Wahab, Siti Nurfarizza (Faculty of Computer and Mathematical Sciences, 2015)
This studies is about recommending food for the anemia patient by using rule base. Anemia is a blood disorder diseases which is having low iron level in the blood. The rule base technique is applied in this studies to recommend suitable food for the anemia patient, as the anemia patient having problem to consume food that can help to increase the iron level in the blood. The aim of this studies is to develop the prototype for recommending food for the anemia patient by using rule base. The first objective of this studies is to gathered food information from the dietician, an interview is being held in order to get further information and a better understanding about Malaysian foods. The second objective of this studies is to analyse the relationship between the suitable food and the preferences of the animatic user by using rule based. The third objective is to create and embedded the rules to the prototype to recommends foods to the animatic users. This studies consists of four phases for methodology, which is data gathering, data analysis, design and implementation. In the first phases, which are data gathering, interview with the dietician is conducted to gather the information regarding the food information as well as the iron level needed daily for the anemia patient. Data analysis is the second phases of methodology in this studies, the gathered data is being analyse and preprocess to produce cleaned data. The third phases is design, the design of the database, interface of the prototype is being done in this phase. The last phases is implementation which are implementing the generated rule base for recommending food to the anemia patient to the prototype. The phases of this methodology is to achieve the objective of this studies and fulfilled the aim of this studies. The final result of this studies is the developed system prototype is able to recommend suitable food for the anemia patient base on the animatic preferences.